Osobowościowe uwarunkowania modyfikacji ciała na przykładzie "współczesnych prymitywistów" - Dolińska-Zygmunt, Grażyna; Szuszkiewicz, Milena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The subject of this article is the analysis of the issues of body modifying concerning "modern primitives". This article is a survey of the basic patterns of body modifying and also mentions the outcome of the studies on the influence of the personality on body modifying. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 230-237